Sociological reading in the phenomenon of the death and extinction of languages - Baha, Fathi (Social Empowerment Journal, 2021)
The conflict between languages reduces the use of languages between people to gradually fade away, leading to an end. It’s until she’s dead and gone. Thus, the death of languages is an incontrovertible fact, and languages in this form of living beings experience the friction, intermarriage, clash and struggle for influence, control, survival, life, death or demise. In this intervention, we will therefore aim to study the phenomenon of the death and extinction of languages. And what is it? What are the main reasons? What mechanisms should be adopted to keep languages from dying?